Ribbon synapse plasticity in the cochleae of Guinea pigs after noise-induced silent damage. - Lijuan Shi; Lijie Liu; Tingting He; Xiaojing Guo; Zhiping Yu; Shankai Yin; Jian Wang (PLoS ONE)
Noise exposure at low levels or low doses can damage hair cell afferent ribbon synapses without causing permanent threshold shifts. In contrast to reports in the mouse cochleae, initial damage to ribbon synapses in the cochleae of guinea pigs is largely repairable. In the present study, we further investigated the repair process in ribbon synapses in guinea pigs after similar noise exposure. In the control samples, a small portion of afferent synapses lacked synaptic ribbons, suggesting the co-existence of conventional no-ribbon and ribbon synapses. The loss and recovery of hair cell ribbons and post-synaptic densities (PSDs) occurred in parallel, but the recovery was not complete, resulting in a permanent loss of less than 10% synapses. During the repair process, ribbons were temporally separated from the PSDs. A plastic interaction between ribbons and postsynaptic terminals may be involved in the reestablishment of synaptic contact between ribbons and PSDs, as shown by location changes in both structures. Synapse repair was associated with a breakdown in temporal processing, as reflected by poorer responses in the compound action potential (CAP) of auditory nerves to time-stress signals. Thus, deterioration in temporal processing originated from the cochlea. This deterioration developed with the recovery in hearing threshold and ribbon synapse counts, suggesting that the repaired synapses had deficits in temporal processing.